(untitled) (Research, Society and Development, 2023)
This study aimed to analyze the reasons for non-adherence to antiretroviral treatment among patients followed at the University Hospital Professor Alberto Antunes - Federal University of Alagoas. This is a descriptive cross-sectional study carried out through semi-structured interviews applied to the first 15 users monitored at the Specialized Outpatient Service with a history of non-adherence who returned to the service from January to May 2023. The results showed a predominance of aged 20 to 39 years (73.3%), male (60%); regarding sexual orientation, 40% declared themselves to be heterosexual, 40% homosexual and 20% bisexual; 100% were brown or black; 60% single, 26.7% married, 13.3% in a stable relationship; 60% lived in the countryside. Only 20% worked, one received more than 1 minimum wage; 33.3% had completed high school and none had higher education. Antiretroviral treatment initiation time of less than 6 months, 6 months to 5 years, 6 to 10 years and more than 10 years was observed, respectively, in 13.3%, 33.3%, 33.3% and 20% of respondents. Reasons for adherence failure: depression (46.7%), lack of motivation (13.3%), access difficulties due to living in a distant city (20%), adverse effects (13.3%), alcoholism (6.7 %). In view of the results, it appears that aspects related to the mental health of people living with HIV/AIDS, especially depression, have an important influence on non-adherence to treatment. The organization of the service and the assistance model are of fundamental importance to guarantee access and adequate approach to intercurrences, with resolution of difficulties that interfere with adherence.